2020
DOI: 10.1016/j.clae.2020.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of the corneal epithelium after overnight wear of orthokeratology contact lenses for myopia reduction

Abstract: Background: To investigate changes in the corneal thickness profile in juvenile myopia after overnight wear of orthokeratology lenses (OK). Methods: A total of 53 juveniles (53 right eyes) successfully wore OK between January 2016 and July 2017 and they were reviewed one day, one week and one month after first wearing it. Epithelial and corneal data were obtained by optical coherence tomography (OCT). Changes in uncorrected visual acuity, refractive error, corneal refractive power, and epithelial and corneal t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 25 publications
4
46
1
1
Order By: Relevance
“…Results on the changes in thickness at the central cornea were also in agreement with previous studies using AS-OCT, which reported significant CCT and CET reduction after commencement of ortho-k lens wear in children. [12][13][14] The magnitude of observed reduction in CET was also comparable. The current study showed that increasing the compression factor by 1.00 D could induce a significantly higher amount of central epithelial thinning (reduction of CET of 6.64 AE 3.29 lm in CCF eyes and 7.98 AE 3.06 lm in ICF eyes).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Results on the changes in thickness at the central cornea were also in agreement with previous studies using AS-OCT, which reported significant CCT and CET reduction after commencement of ortho-k lens wear in children. [12][13][14] The magnitude of observed reduction in CET was also comparable. The current study showed that increasing the compression factor by 1.00 D could induce a significantly higher amount of central epithelial thinning (reduction of CET of 6.64 AE 3.29 lm in CCF eyes and 7.98 AE 3.06 lm in ICF eyes).…”
Section: Discussionmentioning
confidence: 53%
“…Anterior segment OCT has been used to investigate corneal changes after ortho-k lens wear in children. [12][13][14] These studies confirmed that ortho-k lens wear induces central corneal thinning, but conflicting results were found for peripheral corneal changes. Two studies 12,13 reported significant thickening in the peripheral (5-6 mm) cornea, but one observed insignificant changes.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…33,34 Different from the regular alignment fit of the RGP lens, the shape of the OK lens and the inherent tight bending between the lens and cornea can induce central corneal epithelial thinning and surface cell damage, which predisposes the cornea to an increased risk of infection. 35,36 On the basis of different designs of the same material, Wei et al 37 suggested that the OK lens produces a higher risk of microbial keratitis than the alignment fit RGP lens with overnight wearing because the OK lens resulted in greater cornea binding for pathogens in their study. Choo et al 38 stated that tear pooling under the reverse curve of the OK lens created higher colonization rates than the alignment fit lens, under which the tear fluid was evenly distributed.…”
Section: Discussionmentioning
confidence: 99%